De trajetos docentes e de uma travessia : uma história sobre florescer contada por professores de inglês e espanhol em formação inicial do Programa Residência Pedagógica/UFPB - Andrade, Barthyra Cabral Vieira de (2024)
Human development is a complex phenomenon, and so is the development of teachers. This research addresses teaching and its objective is to investigate the development of English and Spanish teachers in initial education, within the scope of the Pedagogical Residency Program, from their representations about teaching, taken in three dimensions: the initial education process, the teaching activity and professionalization. The study is situated in Applied Linguistics (Celani, 2008; Kleimann, 2013; Moita Lopes, 2006, 2013), whose theoretical bases make it possible to give visibility to processes, different individuals involved in them, and their relationships, as well as to propose an understanding of social life. The theoreticalmethodological framework of Socio-Discursive Interactionism (Bronckart, 1999, 2006a, 2006b, 2006c, 2008, 2013, 2021; Bronckart; E. Bronckart, 2017, Bronckart, Machado, 2004, Bulea, 2010, Machado, Bronckart, 2009) was adopted because this field of study places central importance on language, considering it fundamental for understanding human development and the representations that reveal it. Through the conceptual apparatus and textual layering that guide analyses in SDI, it was possible to investigate the representations that the residents, research collaborators, constructed about their actions in texts from two PRP evaluation meetings held in 2019, which were audio-recorded, and in which a dialogue between residents and teacher-educators was established regarding the work developed. The analysis also resulted from the study and interpretation of data based on concepts from Work Sciences (Amigues, 2004; Clot, 2007; 2010; Faita, 2004; Saujat, 2004; Schwartz, 2002), especially the concepts of professional genre, activity, and the role of linguistic practices in work. In seeking the representations of the teachers' actions in the texts, the linguistic-discursive categories of voices and modalizations, as proposed by Bronckart (1999), were used, with special attention given to the relationship between the research results and the conception of teacher education in which I believe. From the analysis of the excerpts three themes and thirteen sub-themes were revealed related to the representations of the actions of the teachers and their development. The results highlight that the work in the PRP shifted from the prescribed formative perspective to a space for teacher development, enabling the existence of individuals capable of critically and actively occupying their professional spaces and their place in the world. Thus, the experience in the program was characterized by the resignification of teaching, resulting in emancipatory practices through which these teachers became aware of their education as transformative, capable of provoking the ontogenesis of their social role as teachers, collaborative and ethical teaching activity, and the development of professionalization as a space of struggle.